Teknik Penilaian Portofolio Dapat Meningkatkan Hasil Belajar Anatomi Fisiologi - I Nyoman Ribek; I Gusti Ketut Ngurah (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2016)
This Study was aimed at finding out the effect of technique assessment of portofolio for Physiological Anatomy learning achievement. This study was a quasi-experimental research involving 80 students of the Department of Health Care of Politeknik Kesehatan Denpasar as the sample. The data were analyzed using analysis of covariance. The result showed that the Physiological Anatomy learning achievement of the group of students who were assessed by portfolio assessment was higher than that of those assessed by performance assessment